The Role of the Denpasar Police Drug Investigation Unit in Handling the Crime of Narcotics Abuse by Foreign Citizens - Evander Clinton Maail (Indonesian Journal of Police Studies, 2021)
Cases of drug abuse in Indonesia are increasing day by day. Denpasar City as one of the world's destinations has become a cross-country drug distribution route. The Denpasar Police Narcotics Satres as law enforcers for narcotics crimes are now not only dealing with local narcotics abusers but also perpetrators with other citizens. Therefore, the purpose of this study is to find out the role of the Denpasar Police Narcotics Unit in handling criminal acts of narcotics abuse by foreigners in the Denpasar Police Legal Area. This research is a field research using a qualitative approach. Theories used in this research include George R. Terry's Management Theory and SWOT Analysis Theory. The results of this study indicate that in handling the crime of narcotics abuse by foreigners, the Narcotics Unit has problems in the paradox of the quantity and quality of personnel. The need for translators that should have been allocated from DIPA has also not been fulfilled. The method under investigation is still manual and inversely proportional to the investigation that started using the application. The role of the Narcotics Satres in handling cases was carried out well with an assessment of the best case handling at the Bali Police. Then the supporting factors for this activity consist of support for the updated law, adequate budget support even though there is no allocation for translators, technological advances that can be used in handling cases and community support as informants. While the inhibiting factors include the lack of certification so that the quality of personnel is not optimal, the method is still conventional and does not use technology, attacks by NGOs that are critical of the actions of the Police and the weak legal culture in Indonesia so that it is often misused in handling narcotics cases.